Examining the Effects of Different Types of Achievement Goal Orientation on Undergraduate Students’ Engagement in Distance Learning: The Mediating Effect of Self-Efficacy - Tingzhi Han; Guoxing Xu; Wenli Lu (Behavioral Sciences)
This study investigates the impact and mechanisms of achievement goal orientation on online learning engagement among undergraduates, using a sample of 461 students enrolled in online courses from four universities of varying levels in Shanghai, China. Self-efficacy is introduced as a mediating variable, and structural equation modeling is employed to assess the effects. The findings reveal that different types of achievement goals have varying natures and intensities in their associations with undergraduate online learning engagement. Self-efficacy partially mediates the effect of mastery-approach goals on online learning engagement, but does not mediate the effects of mastery-avoidance, performance-approach, or performance-avoidance goals. The study recommends leveraging the guiding role of mastery-approach achievement goals to help students set scientific and reasonable goals, and stimulating students’ self-efficacy through the dual influences of external support and internal motivation. With the support of these strategies, significant improvements in undergraduate online learning engagement can be achieved.